2012
DOI: 10.1021/ja209334v
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for CH···π Interaction Mediated Stabilization of Pro-cisPro Bond in Peptides with Pro-Pro-Aromatic motifs

Abstract: Although weak interactions play subtle but important roles in dictating protein structures, their experimental detection is nontrivial. From NOE experiments we provide direct evidence for the presence of CH···π interaction, operational between the C(α)-H of the first Pro and the aromatic (Aro) side chain of Xaa, in a peptide series with the general sequence Ac-Pro-Pro-Xaa-NH(2). Indirect evidence of CH···π interaction is provided from ring current-induced upfield displacement of Pro(1) C(α)-H chemical shifts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(96 citation statements)
references
References 49 publications
8
87
1
Order By: Relevance
“…The trends in ellipticity vs. temperature generally agreedw ith those observedf or proline-rich PPII helices, specifically that the mean residue ellipticity (MRE) values decreased as af unction of increasing temperature. [29] Nevertheless, we concluded that the thermal stabilities of PPII helices in structures featuring peptoid and proline mutants were similar.N otably,i ncorporation of peptoid residues in two sequences (cTp_XE and cTp_XP) did not diminish the stability of PPII helical structure, as both mutation sets appeared to slightly enhance the thermal stabilityo ft he helical positions. [29] Nevertheless, we concluded that the thermal stabilities of PPII helices in structures featuring peptoid and proline mutants were similar.N otably,i ncorporation of peptoid residues in two sequences (cTp_XE and cTp_XP) did not diminish the stability of PPII helical structure, as both mutation sets appeared to slightly enhance the thermal stabilityo ft he helical positions.…”
Section: Synthesis and Characterization Of Pxxp Mimetic Trpplexus Seqsupporting
confidence: 77%
See 1 more Smart Citation
“…The trends in ellipticity vs. temperature generally agreedw ith those observedf or proline-rich PPII helices, specifically that the mean residue ellipticity (MRE) values decreased as af unction of increasing temperature. [29] Nevertheless, we concluded that the thermal stabilities of PPII helices in structures featuring peptoid and proline mutants were similar.N otably,i ncorporation of peptoid residues in two sequences (cTp_XE and cTp_XP) did not diminish the stability of PPII helical structure, as both mutation sets appeared to slightly enhance the thermal stabilityo ft he helical positions. [29] Nevertheless, we concluded that the thermal stabilities of PPII helices in structures featuring peptoid and proline mutants were similar.N otably,i ncorporation of peptoid residues in two sequences (cTp_XE and cTp_XP) did not diminish the stability of PPII helical structure, as both mutation sets appeared to slightly enhance the thermal stabilityo ft he helical positions.…”
Section: Synthesis and Characterization Of Pxxp Mimetic Trpplexus Seqsupporting
confidence: 77%
“…[18] Units are in mean residue ellipticity (MRE, deg cm 2 dmol À1 res À1 ). [29,30] Therefore, in select cases such as the TrpPlexus fold, prolinec ompatibilityw ith the PPII helix is not guaranteed. B) Far-UVC Dt hermal melts monitoring meanresidue ellipticity at 228 nm as af unction of temperature for sequencese xhibiting PPII helical content(100 mm,1mm pathl ength, 10 mm PBS buffer, pH 7.5).…”
Section: Design Of Pxxp Mimetic Trpplexussequencesmentioning
confidence: 99%
“…911,20,21,23,46 cis-Pro-Aromatic interactions can result from the aromatic ring interacting with the preceding proline ring, or from the aromatic ring interacting with Hα two residues prior to it (H α ( i −2)-cis-Pro-Aromatic( i ) interactions), which involves a cis prolyl amide bond (Figure 2). 1,68,20 Studies by Creighton and Basu indicated that cis-Pro-Aromatic interactions, primarily with H α ( i −2) of Gly or Pro two residues prior to Tyr/Trp/Phe, are enthalpically favorable and dependent on electronics of the aromatic residue.…”
Section: Local Aromatic-proline Interactionsmentioning
confidence: 99%
“…1,68,20 Studies by Creighton and Basu indicated that cis-Pro-Aromatic interactions, primarily with H α ( i −2) of Gly or Pro two residues prior to Tyr/Trp/Phe, are enthalpically favorable and dependent on electronics of the aromatic residue. 10,11,20,22,23 Aromatic-Pro-aromatic sequences also exhibit a high propensity for cis amide bonds, with aromatic rings able to stack against both faces of the proline ring. 8 Interestingly, Dyson and Wright found that in SYPXDV peptides, the highest population of cis amide bonds was observed with Phe, rather than Tyr or Trp, at the X position.…”
Section: Local Aromatic-proline Interactionsmentioning
confidence: 99%
See 1 more Smart Citation